Universal Service Obligations in Utility Concession Contracts and the Needs of the Poor in Argentina's Privatizations - Estache, Antonio 1957- (The World Bank, 1999)
The structural changes that come with privatization may induce a reconsideration of the regulations defined during the early stages of privatization. - Chisari and Estache summarize the main lessons emerging from Argentina's experience, including universal service obligations in concession contracts. They discuss free-riding risks, moral hazard problems, and other issues that arise when social concerns are delegated to private operators. After reporting on Argentina's experience, Chisari and Estache suggest some guidelines: · Anticipate interjurisdictional externalities. Users' mobility makes targeting service obligations difficult. · Minimize the risks imposed by elusive demand. In providing new services, a gradual policy may work better than a shock. · Realize that unemployment leads to delinquency and lower expected tariffs. Elasticity of fixed and usage charges is important. · Deal with the fact that the poor have limited access to credit. Ultimately, plans that included credit for the payment of infrastructure charges were not that successful. · Coordinate regulatory, employment, and social policy. One successful plan to provide universal service involved employing workers from poor families in infrastructure extension works. · Beware of the latent opportunism of users who benefit from special programs. Special treatment of a sector may encourage free-riding (for example, pensioners overused the telephone until a limit was placed on the number of subsidized phone calls they could make). · Fixed allocations for payment of services do not ensure that universal service obligations will be met. How do you deal with the problem that many pensioners do not pay their bills? · Anticipate that operators will have more information than regulators do.